Treatment of Traumatic Brain Injury in Morepork Owls: A Review of Diagnostic and Treatment Options - Jolly, Megan (Wildlife Rehabilitation Bulletin, 2017)
The Morepork (Ninox novaeseelandiae) is a small owl (150–200 g adult weight) of the family Strigidae. It is common throughout most of New Zealand and closely related to the Southern boobook (Ninox boobook) and Tasmanian boobook owls (Ninox leucopsis) found in Australia. Morepork are commonly presented to the Wildbase Hospital at Massey University, New Zealand. The vast majority of admissions are related to traumatic injuries with many showing some degree of neurological dysfunction. This review of case records indicates that only 35% of morepork admitted with a traumatic brain injury (TBI) recovered to the point of release. A failure to return to normal neurological function could be the result of direct trauma to neurological tissues acquired at the time of impact or ongoing damage with altered physiology compounding the initial trauma. While little can be done to treat primary brain insults, treatments that target minimizing secondary brain injury can improve the outcome of TBI. Diagnostic and treatment options for TBI in human and small animal medicine were reviewed for their potential application to avian medicine with the aim of improving treatment of TBI cases in morepork that will increase recovery rates and long term survival of birds returned to the wild.